Brief overview of the currently available COVID-19 vaccines / Anna Krasilnikova - Krasilnikova, Anna (Faculty of Medicine, 2022)
The ongoing pandemic COVID-19, coupled with the absence of an effective antiviral treatment against SARS-CoV-2 is forcing the world community to focus on the specific prevention of COVID-19. Mass immunization, along with other public health measures, can reduce morbidity and mortality and reduce the burden of economic and social losses due to the global spread of Covid-19. Currently, more than 30 vaccines have already been authorised, and more than 60 candidates are now in clinical trials phases III. This review summarises and classify the current information about available vaccines and briefly describes their mechanisms of action, safety, and potential benefits and drawbacks. This paper also provides a brief overview of the present data of phases III COVID-19 vaccines clinical trials, summarised in the table and focusing mainly on their demographic data and clinical effectiveness.